Students’ Internship Towards Workplace Resilience and Adaptability of BSBA Human Resource Management: Its Job Absorption - Escario, Charlene; Matti, Jennifer Khate; Provedincia, Jesica; Rumbawa, Katherine; Tolentino, Regine; Notario, Rheanne Bereyll; Padua, Shakira Aisteru (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the workplace resilience, adaptability, and job absorption of Bachelor of Science in Business Administration major in Human Resource Management student interns based on the assessments of the student interns, faculty members, and the on-the-job training coordinator. It was conceptually anchored in the view that internship experiences provide opportunities for developing the behavioral and psychological qualities needed for workplace readiness and employment. A descriptive-correlational research design and cross-sectional survey method were employed. The respondents comprised 91 participants, including 80 student interns, 10 faculty members, and one OJT coordinator, selected through stratified, purposive, and convenience sampling. Data were gathered using a researcher-made questionnaire evaluated by the research adviser and faculty experts. Percentage, ranking, weighted mean, and Analysis of Variance were used to analyze the data. Results showed that the student interns were generally resilient, with a consolidated weighted mean of 3.87; adaptable, with a mean of 3.76; and absorbed in their work, with a mean of 3.53. Social support received the highest composite rating for workplace resilience, continuous learning ranked highest for adaptability, and concentration and focus ranked highest for job absorption. However, emotional resilience and time distortion received comparatively lower ratings, indicating areas requiring further development. No significant differences were found among the assessments of the three respondent groups regarding workplace resilience and adaptability, showing consistency in their perceptions. Internship experiences also provided preparation for employment opportunities in strategic planning, organizational development, talent acquisition, compensation, payroll, and employee relations. The study concluded that internships positively contributed to workplace competence, engagement, employability, and professional readiness. It recommended stronger mentoring, monitoring, feedback, specialized training, career development activities, industry-academe collaboration, and continuous program evaluation. The study supports SDG 4 - Quality Education and SDG 8 - Decent Work and Economic Growth by promoting relevant experiential learning and preparation for productive employment. Its sustainability impact lies in strengthening educational quality, institutional collaboration, workforce readiness, and long-term socio-economic participation.